177Lu‐DOTMP induces G2/M cell cycle arrest and apoptosis in MG63 cell line. (11th July 2018) - Kumar, Chandan; Sharma, Rohit; Das, Tapas; Korde, Aruna; Sarma, Haladhar; Banerjee, Sharmila; Dash, Ashutosh
Abstract : Bone pain is the major manifestation of skeletal metastases. Although various treatment modalities are available for bone pain palliation, use of radiolabeled phosphonates is documented to be more effective. Among radionuclides available for this purpose, lutetium‐177 is gaining popularity due to its moderate beta energy, theranostic capability, favorable half‐life and convenient production logistics. 177 Lu‐DOTMP has shown considerable promise as a metastatic bone pain palliating agent in preliminary evaluations and recent clinical studies. Therefore, an attempt was made to elucidate the possible mechanism of in vitro cell death induced by 177 Lu‐DOTMP in MG63 cells. 177 Lu‐DOTMP binding studies were carried out in mineralized bone of MG63 cells and around 50% binding was observed. Skeletons of Wistar rats showed 1.78 ± 0.5% IA/g at a 3 h time period which was almost constant up to 7 days. MG63 cells were incubated with 3.7 and 37 MBq of 177 Lu‐DOTMP for 48 h prior to perform assays. An increase in the magnitude of cell toxicity and apoptotic DNA fragmentation was observed. Enhancement of G2/M phase cell cycle arrest and apoptosis were documented which were dose‐dependent. Thus, 177 Lu‐DOTMP induced apoptotic cell death in MG63 cells, which might be one of the primary causes of pain relief in osseous metastases. Abstract : MG63 cells treated with 37 MBq of 177 Lu‐DOTMP for 48 hours were compared with control cells. Cell cycle phase and apoptotic cell death were analyzed by flowcytometer. 177 Lu‐DOTMP induces G2/M cell cycle phase arrest and apoptotic cell death in MG63 cells.